Fill in the blanks to make the following statements true:

(i) (-5) + (-8) = (-8) + (………)

(ii) -53 + …….= -53

(iii) 17 + ……. = 0

(iv) [13 + (-12)]+(……..) = 13 +[(-12)+(-7)]

(v) (-4) + [15+(-3)] = [-4+15] + ……

(i) We have,

(-5) + (-8) = (-8) + (…..)

So,

(-5) + (-8) = (-8) + (-5)

(ii) We have,

- 53 + (…..) = - 53

So,

- 53 + (0) = - 53

(iii) We have,

17 + (…..) = 0

So,

17 + (-17) = 0

(iv) We have,

[13 + (-12)] + (…..) = 13 + [(-12) + (-7)]

So,

[13 + (-12) + (-7) = 13 + [(-12) + (-7)]

(v) We have,

(-4) + [15 + (-3)] = [(-4) + 15] + (…..)

So,

(-4) + [15 + (-3)] = [(-4) + 15] + (-3)

10